Efektivitas dan Efisiensi Pemungutan Serta Kontribusi Pajak Mineral Bukan Logam dan Batuan Terhadap Pajak Daerah Kabupaten Musi Banyuasin - Farida Aryani; Deswati Supra (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2020)
This study discusses the analysis of the effectiveness and efficiency of tax collection and the contribution of nonmetallic minerals and rocks to local taxes. Determination of local tax revenue targets does not match the actual potential and the achievement of nonmetallic mineral and rock tax revenue targets have not been effective so that it will have an impact on the contribution of tax revenues on nonmetallic minerals and rocks. The methods used in this research are quantitative and qualitative methods. The data used are primary and secondary data. The results of this study explain that the level of effectiveness of tax collection of nonmetallic minerals and rocks to the local tax of Musi Banyuasin Regency from 2015 to 2019 is in the category of very effective with an average ratio of 115.82%. The ratio of nonmetallic mineral and rock tax efficiency to the local tax of Musi Banyuasin Regency from 2015 to 2019 is in the criteria of very efficient with an average ratio of 18.17%. The contribution of nonmetallic mineral and rock taxes to regional tax revenue is still lacking, where in 2015 to 2019 the tax on nonmetallic minerals and rocks has an average value of 1.53%.